ISTANBUL AS A (RE)TURNING POINT - Funda CİVELEKOĞLU (Fırat University, 2019)
“Spatial turn” that has happened in the 1980s has influenced the development of not only social sciences, but also literary studies. “Topographical turn,” that has an increasing influence on cultural and literary studies since the beginning of 2000s is coined by the German theoretician, Sigrid Weigel. Accordingly, focusing on the spatial charactersictics of literary texts, symbolic topographical figures have contributed to the formation of an imaginative counter discourse. Topographical turn that relates to cultural geography to provide an interdisciplinary outlook and deals with how settings of literary texts are associated with the cultural and historical contexts of the places. The screenwriter Ümit Ünal received the best screenwriter award from Milliyet Newspaper Screenplay Competition in 1986 with the script of My Aunt and it was filmed by Halit Refiğ the following year. In this article, I aim to explore how Istanbul functions in the film as a literary character. The movie presents a sketch of Üftade’s life from her nephew Umur’s point of view through flashbacks and Umur, as the narrator of the story, feels the urge to tell her story. Umur’s parents move to his grandmother’s house in Istanbul and Umur spends most of his time with his Aunt. Soon after they become confidants and their adventures are mostly set in Istanbul. Istanbul has a